2013
DOI: 10.1007/s12013-013-9698-1
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effects of Bone Marrow-Derived Mesenchymal Stem Cells and Simvastatin in a Rat Model of Liver Fibrosis

Abstract: Liver fibrosis is the excessive accumulation of extracellular matrix (ECM) proteins including collagen that occurs in most types of chronic liver diseases. Studies concerning the capacity of mesenchymal stem cells (MSCs) and simvasatain (SIMV) to repair fibrotic tissues through reducing inflammation, collagen deposition, are still controversial. This study aimed to investigate the therapeutic efficacy of bone marrow (BM)-derived MSCs and SIMV on carbon tetrachloride (CCl4)-induced liver fibrosis in rats. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…Motawi et al . (92) also established that MSCs administered at the cessation of injury can lead to a reduction in fibrosis and allied this to a significant increase in MMP‐1 ( P < 0.01) and a decrease in TIMP‐1 ( P < 0.001). They administered syngeneic BM‐MSCs via the tail vein of CCl 4 ‐injured rats (intraperitonially twice a week for 6 wk) 1 d after the cessation of injury and analyzed the effects 8 d later.…”
Section: Do Mscs Prevent Fibrosis Rather Than Promote Its Resolution?mentioning
confidence: 82%
See 1 more Smart Citation
“…Motawi et al . (92) also established that MSCs administered at the cessation of injury can lead to a reduction in fibrosis and allied this to a significant increase in MMP‐1 ( P < 0.01) and a decrease in TIMP‐1 ( P < 0.001). They administered syngeneic BM‐MSCs via the tail vein of CCl 4 ‐injured rats (intraperitonially twice a week for 6 wk) 1 d after the cessation of injury and analyzed the effects 8 d later.…”
Section: Do Mscs Prevent Fibrosis Rather Than Promote Its Resolution?mentioning
confidence: 82%
“…It is not possible to extract a consistent profile of effects on MMPs as a result of inconsistencies in what has been tested. Nevertheless, syngeneic rodent MSC treatment in models of CCl 4 ‐induced liver injury leads to increased expression of MMP‐1/13 (78, 79, 92) and MMP‐12 (83), a reduction in expression of MMP‐2 (84, 86), and no or limited effect on MMP‐9 (78, 83, 86) in the setting of resolving fibrosis. What remains unclear is whether these fluxes in MMPs reflect maturation/changes in the inflammatory infiltrate (45, 97), including HSCs, neutrophils, macrophages, and dendritic cells (driven by MSCs), or whether MSCs actually secrete MMPs themselves.…”
Section: Can Mscs Deliver a Direct Antifibrotic Effect?mentioning
confidence: 99%
“…Simvastatin, through the activation of the endothelial KLF2-nitric oxide pathway, is the most effective statin protecting the hepatic endothelium in cirrhosis 13. Moreover, previous reports suggested that statins may improve HSC phenotype,6 14 15 however, the possible direct role of KLF2 improving HSC function and liver fibrosis has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to small numbers of heterogene- to CCl4-treated rats (Jung et al 2009;Li et al 2013;Seo et al 2014) Reduced fibrosis, TGF-β, EMT, and improved liver function UC-MSC transfusion in PBC patients with an incomplete response to UDCA No obvious side effects Bone marrow-derived mesenchymal stem cells (BMMSCs) in CCl4-treated rats (Motawi et al 2014) Reduced fibrosis markers and inflammatory cytokines BM-MSCs in patients with alcoholic cirrhosis (Jang et al 2014) No significant side effects. Histological improvement, reduced TGF-β, collagen I, α-SMA (c) Antagonizing TGF-β and CTGF EW-7197 in CCl4-treated mouse, BDL rat, bleomycin mouse, and unilateral ureteral obstruction mouse models (Park et al 2014) Attenuated myofibroblast activation and ECM accumulation, blockade TGF-β1/Smad2/3 and ROS signaling Not applied for liver fibrosis Human bone morphogenic protein-7 (rhBMP-7) in porcine serum-treated rats (Zhong et al 2013 ous patients tested, the potential effects of this therapy remain unclear (Pellicoro et al 2014).…”
Section: Anti-fibrotic Strategies That Reduce Inflammation and The Immentioning
confidence: 99%
“…A pilot study investigated the safety and efficacy of UC-MSC transfusion in primary biliary cirrhosis (PBC) patients and indicated that UC-MSC transfusion is feasible and well tolerated in patients . The other study indicated that transplantation of bone marrow-derived mesenchymal stem cell (BM-MSC) therapy for the treatment of liver fibrosis in CCl4-treated rats is effective (Motawi et al 2014). Additionally, the clinical therapy in patients with alcoholic cirrhosis using BM-MSC induced a histological and quantitative improvement in hepatic fibrosis (Jang et al 2014).…”
Section: Management Of Other Immune Cells: Previous Reportsmentioning
confidence: 99%